AGROCROWDING - Rajeev M, Bhaskar N, Jagan P J, Aravindhan N, Subramanian N (International Journal of Advanced Science and Technology, 2020)
Crowdsourcing, understood as outsourcing tasks or data collection by a large group of non- professionals, is increasingly used in scientific research and operational applications. Using this approach a crowd sourcing platform for agriculture is developed. It consists of four type of users namely Worker, Requester, Agriculture Expert and Database Administrator. In this community both the Worker and Requester are Farmers. The requester is looking for answer in the forum where they post the questions to the community in which the worker will respond to those question as per their knowledge as they are also the fellow farmers. The technical expert evaluates each and every solution and when they are verified as true it will be displayed to the farmers. Once displayed they are stored in the database. Whenever the same type of question arises, using data analytics the data sets are scanned using Association Rules and the frequent pattern is generated using any one of association rules and the results which matches the question of requester is displayed. We can store and retrieve the historical or past data from the database. Through this application the Requester need not wait for the worker response as they tend to get the results automatically from the database when the queries are posted in the community which brings more solutions and they are time efficient